2021
DOI: 10.1002/app.51647
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of pH‐responsive cellulose nanofibril/sodium alginate based hydrogels for drug release

Abstract: In this work, hydrogels composed of cellulose nanofibril (CNF) and sodium alginate (SA) were prepared as a pH-responsive release system by controlling the amount of CNF and SA. Scanning electron microscopy, thermogravimetric analysis, and swelling rate methods were used to characterize. The results showed that when the mass ratio of CNF to SA was 2:1, CNF/SA hydrogels with better morphology were obtained. Due to the deprotonation or protonation of calcium alginate, as the pH changing from 1.5 to 11.0, the swel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Experimental data evidence that all the samples reach an equilibrium condition after 4 hours, with swelling ratio values higher than 100%. The presence of cellulose appears to increase the swelling capacity of the material; this behaviour has already been observed in other studies and ascribed to the hydrophilic characteristics of cellulose 42,43 . On the other hand, soybean peroxidase is a water-soluble globular protein able to to form electrostatic interactions with the surrounding environment 44 .…”
Section: Hydrogels Preparation and Characterisationsupporting
confidence: 77%
“…Experimental data evidence that all the samples reach an equilibrium condition after 4 hours, with swelling ratio values higher than 100%. The presence of cellulose appears to increase the swelling capacity of the material; this behaviour has already been observed in other studies and ascribed to the hydrophilic characteristics of cellulose 42,43 . On the other hand, soybean peroxidase is a water-soluble globular protein able to to form electrostatic interactions with the surrounding environment 44 .…”
Section: Hydrogels Preparation and Characterisationsupporting
confidence: 77%
“…The regression coefficients (r) for the Korsmeyer–Peppas model with varying concentrations of AMPS (CAAM-1, CAAM-4, CAAM-6) confirmed that the release mechanism is controlled by diffusion. Based on the Korsmeyer–Peppas model, the release exponent ( n ) values of all hydrogels (CAAM-1, CAAM-2, CAAM-3, CAAM-4, CAAM-6, CAAM-7, CAAM-9) were between <0.5, indicating a Fickian diffusion process [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In FTIR spectrum of the CA/SA hydrogel, the distinctive peak appeared at 1571 cm −1 is assigned to the carboxylate groups [17]. Moreover, an appeared peak at 1169 cm −1 can be attributed to the C-O-C stretching vibration [18][19][20].…”
Section: Resultsmentioning
confidence: 99%